2020
DOI: 10.1186/s13046-020-01701-z
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal dysfunction and autophagy blockade contribute to autophagy-related cancer suppressing peptide-induced cytotoxic death of cervical cancer cells through the AMPK/mTOR pathway

Abstract: Background Autophagy is an intracellular process through which intracellular components are recycled in response to nutrient or growth factor deficiency to maintain homeostasis. We identified the peptide autophagy-related cancer-suppressing peptide (ARCSP), a potential antitumor peptide that disrupts intracellular homeostasis by blocking autophagic flux and causes cytotoxic death. Methods The proliferative ability of ARCSP-treated cervical cancer cells was examined by the CCK8, EdU, and colony formation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 47 publications
6
32
0
Order By: Relevance
“…Many studies have found that the destruction of mTOR leads to the suppression of the cell cycle and angiogenesis, thereby inhibiting the development of cervical cancer. These studies also validated the reliability of our results ( Bossler et al, 2019 ; Sun et al, 2020 ; Yang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have found that the destruction of mTOR leads to the suppression of the cell cycle and angiogenesis, thereby inhibiting the development of cervical cancer. These studies also validated the reliability of our results ( Bossler et al, 2019 ; Sun et al, 2020 ; Yang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…The changes in lysosomal pH and cathepsin expression illustrated that the lysosomal functions were altered in the 6c-treated system. A recent paper reported that lysosomes are dysfunctional with the decreased expression of LAMP1 and LAMP2 [52]. Interestingly, the expression of LAMP1 and LAMP2 was increased after 6c treatment; however, the fluorescence intensity of AO (red), lyso-tracker, and DND-189 was reduced.…”
Section: Discussionmentioning
confidence: 94%
“…There is evidence that AMPK inhibits the mTOR complex 1 (mTORC1) through the phosphorylation of the tuberous sclerosis complex protein-2 (TSC2) and raptor (36). Furthermore, the AMPK/mTOR pathway plays a crucial role in the progression of various tumors (9,11,37). For example, trifolirhizin induces colorectal cancer cell autophagy and apoptosis through activating AMPK and suppressing the mTOR pathway in vivo and in vitro (9).…”
Section: Discussionmentioning
confidence: 99%